Challenges in claiming under the doctrine of privity contract in Malaysia: the issue of halal - Naimat, Nasihah; Abu Bakar, Elistina; Muhammad Arif, Afida Mastura (Human Resource Management Academic Research Society, 2022)
The doctrine of privity provides that only the contracting parties to a contract incur rights and obligations under the contract. Third parties cannot sue or be sued under a contract. Thus, if a manufacturer who sells a product to a seller who then sells it to a consumer who is injured by the product, the consumer could sue the seller based on the contract of sale between the seller and the consumer. The consumer cannot sue the manufacturer because there is no contract between the consumer and the manufacturer. This article thus addresses the question of the extent to which the doctrine of privity can give rise to liability on the part of the manufacture or the seller on the issue of halal. The findings of this study suggest that the doctrine of privity has some weaknesses that need to be addressed in order to provide better consumer protection on the issue of halal.